LOCAL ORIENTATION WISDOM ON THE BUGIS TRADITIONAL HOUSE LAYOUT IN TOSORA VILLAGE, WAJO - Naidah Naing; Abdul Karim Hadi; Asdar Djamereng (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2018)
Tosora village in Wajoregency-South Sulawesiis the village of the former capital of Wajo Kingdom in the 16th and 17th centuries, which still maintainsthearhitecture of Bugis traditional suspended house. The existence of the historic sites such as oldmosques, fortresses, Geddong and the natural conditions surrounded by rivers, rice fields and lakes is important in the tradition of building Bugis houses in Tosora. The orientation of the layout and house direction in these traditional settlements is various, so the researchaimed to revealthe guidelines used by Tosora peoplein determining the orientation of Bugis Traditional houses either based on tradition or other influencing factors.Theresearch methodology usedqualitative methods with the Case Study Approach. Theresearch wasdescriptive and used the analysis method of Discovering Cultural Themes. The results showed that traditionally, the orientation ofBugis house layout was the direction of thehousesbased on the East wind, the position of the sun on the house and the position of the moon's light into the house. In addition, the orientation is determined by the layout of Bugis house in Tosora which is influenced by the existence of the historic sites (old / ancient mosques and squares) and the location ofthehouses from rice fields(workplaces) for easy accessibility. The moon symbol as a factor that influences the orientation of the house is different from thatin other settlements in Indonesia.